2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25521
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Engineering Leadership Potential During the On-Campus Recruiting Process

Abstract: professional experiences and research interests range from mechanical engineering facilities design to research that applied engineering and molecular biology approaches to the study of the skeletal response to mechanical loading. As a Mechanical Engineer, she worked on facility design projects involving mechanical systems that included heating, ventilation, air conditioning, and energy conservation systems, as well as R&D of air conditioning equipment for Navy ships. Additional research interests have include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Please circle your answer for each student you speak with during the mock career fair activity: On a scale of [1][2][3][4][5] o Articulation of personal leadership development and awareness through experience in internships/co-ops, student organization involvement, or engineering project groups. o Describe how experiences connect to the company; establish a connection with the company o Confidence o List student involvement activities, internships/co-ops, or project groups o Identify an interest in the company o Give the title of a leadership position held with a student organization, internship/co-op position or technical project position o Name a technical engineering project they participated in o Other: ________________________________________________________ (please add any 'others' from above) o Other: ________________________________________________________ (please add any 'others from above) o Other: ________________________________________________________ (please add any 'others from above)…”
Section: Appendix Amentioning
confidence: 99%
See 2 more Smart Citations
“…Please circle your answer for each student you speak with during the mock career fair activity: On a scale of [1][2][3][4][5] o Articulation of personal leadership development and awareness through experience in internships/co-ops, student organization involvement, or engineering project groups. o Describe how experiences connect to the company; establish a connection with the company o Confidence o List student involvement activities, internships/co-ops, or project groups o Identify an interest in the company o Give the title of a leadership position held with a student organization, internship/co-op position or technical project position o Name a technical engineering project they participated in o Other: ________________________________________________________ (please add any 'others' from above) o Other: ________________________________________________________ (please add any 'others from above) o Other: ________________________________________________________ (please add any 'others from above)…”
Section: Appendix Amentioning
confidence: 99%
“…In a previous study 1 , the authors used a qualitative approach to explore recruiters' perspectives on determining engineering leadership potential during busy career fair interactions. With employers consistently ranking leadership as an important characteristic to demonstrate during on-campus recruiting activities 2 , Handley, Lang, and Erdman sought to understand how a student could effectively demonstrate leadership during these busy recruiting activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from Handley, Lang and Erdman (2016) investigated the perspectives of on-campus recruiters who were looking for leadership among engineering students in their final year of studies [10]. They found that recruiters were seeking students who had been involved in activities outside the classroom and had the ability to articulate the learning gained from these experiences.…”
Section: Hiring and Recruiting For Engineering Leadershipmentioning
confidence: 99%
“…They found that recruiters were seeking students who had been involved in activities outside the classroom and had the ability to articulate the learning gained from these experiences. The three engineering leadership themes they identified were communication (selfawareness), connection (big picture thinking) and confidence [10].…”
Section: Hiring and Recruiting For Engineering Leadershipmentioning
confidence: 99%